Microstructure evolution during softening and melting process in different reduction degrees. (January 2016) - Guo, W. T.; Xue, Q. G.; Liu, Y. L.; She, X. F.; Wang, J. S.
Abstract : This paper concerns the degree of indirect reduction in a burden rising substantially in an oxygen blast furnace. It studies the pellet, sinter and a mixture of both in different cases. The paper concerns experiments on single particle load softening to investigate the microstructural evolution of different burdens during the softening and melting process. The results of the experiments show that the degree of reduction impacted the softening and melting behaviour. In the case of a low degree of reduction, a slag phase substrate and a myrmekitic iron structure were formed on the periphery area of the molten burden, whereas slag phase substrate and disperse island wüstite structure were formed in the centre area. Both peripheral and central areas had a slag phase substrate and myrmekitic iron texture. The slag–iron distribution had a structure in which the slag phase was cut in the metal iron phase. The content of 2FeO.SiO2 as a low melting point phase in the slag decreased sharply, and this resulted in the increase in slag–iron separation temperature. The variation of the Ca/Si ratio in the interface between the pellet and the sinter indicated that enhancement of the reduction degree caused the initial temperature of the interaction in the mixed burden to rise and the interaction distance to decrease.